Implementation of Curriculum Management at Private Madrasah Tsanawiyah - Mayasari Mayasari; Neliwati Neliwati; Chandra Wijaya (EDUTEC : Journal of Education And Technology, 2024)
This research investigates curriculum management implementation at a private MTs (Islamic junior high school) in Pantai Cermin sub-district, Serdang Bedagai Regency. Curriculum management is a systematic and cooperative process aimed at achieving educational goals. It operates at two levels: school-wide and classroom. The headmaster plays a key role at the school level, while teachers are crucial at the classroom level. This qualitative descriptive study utilized interviews, observations, and document reviews to gather primary and secondary data. The study involved the principal, deputy principal, teachers, and students as informants. The findings reveal that curriculum management at the school begins with thorough planning and successful implementation. The curriculum used is the 2013 curriculum, enriched with local wisdom and life skills education. External and internal factors support the process, while challenges include some educators' lack of professionalism, passive teaching methods, and substandard teaching tools. The curriculum management strategy focuses on developing a curriculum tailored to the students' and school's specific needs. The implementation has improved education quality, enhanced staff performance, increased public awareness of education's importance, optimized resource management for educators, and encouraged continuous innovation among teachers.